2011
DOI: 10.1088/0957-4484/22/43/435705
|View full text |Cite|
|
Sign up to set email alerts
|

Method for electrical characterization of nanowires

Abstract: The ability to control conductivity in semiconductor nanostructures is often challenged by surface states trapping the majority of the charge carriers. Addressing this challenge requires a reliable method for assessing electrical properties such as carrier concentration and mobility. Unfortunately, here we are facing another challenge, as the Hall effect is geometrically inapplicable to nanowires while the field effect model is also challenged by the geometry of the common nanowire field effect transistor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…As shown in Ref. 58, hydrochloric acid (HCl) removes the native Ga oxide from the nanowire surface, leading to a reduction of both the surface state density and the surface band bending. The nanowire emission measured right after a 30 s HCl etching exhibits a blueshift of 85 meV.…”
Section: Nanowiresmentioning
confidence: 99%
“…As shown in Ref. 58, hydrochloric acid (HCl) removes the native Ga oxide from the nanowire surface, leading to a reduction of both the surface state density and the surface band bending. The nanowire emission measured right after a 30 s HCl etching exhibits a blueshift of 85 meV.…”
Section: Nanowiresmentioning
confidence: 99%
“…While the optical characterization of GaN nanowire and nanorod arrays through spectroscopic ellipsometry (SE) 9,10 , polarized-goniometry 20 or reflectivity spectroscopy 11 is well reported in the literature, the characterization of electrical properties related to conductivity, like carrier concentration and mobility, presents some difficulties associated to the geometry of this kind of structures 4,21 . Up to now, the majority of the studies are focused on Hall effect and field effect measurements performed on single nanowires after fabricating multiple contacts [22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…To use it on nanostructures, the specific structure has to be considered. For example, to characterize nanowires, we need to consider a cylindrical structure of radius R. [25] It can be shown that the electric field at the surface is given by…”
Section: Modelmentioning
confidence: 99%